Determinasi Faktor Psikologis dan Sosial terhadap Perilaku Kekerasan di Dunia Maya pada Remaja: Pendekatan Kuantitatif - Adinda Indriyanti A; Uswatun Hasanah (Journal of Education Psychology and Social Development, 2025)
The rapid development of information technology creates new challenges in the form of cyberbullying, which has a significant impact on mental health, especially the younger generation. This study aims to explore the factors that influence cyberbullying behavior through a survey of respondents selected by purposive sampling. The research instrument covered aspects of attitudes towards cyberbullying, the influence of social media, and the impact on mental health. The results showed that most respondents were neutral towards this phenomenon, but some experienced psychological impacts such as stress and anxiety. This study highlights the importance of early education, supervision, and the establishment of a positive digital environment. The findings are expected to contribute to the scientific literature as well as support public policies to reduce the incidence of cyber violence and its impact on mental health.